Exosomes Derived From M2b Macrophages Attenuate DSS-Induced Colitis - Yang, Ruibing; Liao, Yao; Wang, Lifu; He, Ping; Hu, Yuanjia; Yuan, Dongya; Wu, Zhongdao; Sun, Xi (Frontiers in Immunology, 2019)
Macrophages are commonly classified as M1 macrophages or M2 macrophages. The M2 macrophages are further sub-categorized into M2a, M2b, M2c, and M2d subtypes. The M2a, M2b, and M2c subtypes play roles in anti-inflammatory activity, tissue remodeling, type 2 T helper cell (Th2) activation, and immunoregulation. Previous studies have shown that macrophage exosomes can affect some disease processes. Exosomes are 30–150-nm lipid bilayer membrane vesicles derived from most living cells, with important biological functions. The role of exosomes in preventing the development of autoimmune diseases, including inflammatory bowel disease (IBD), has evoked increasing interest. Here, we analyze the roles of exosomes derived from M2a, M2b, and M2c macrophage phenotypes in dextran sulfate sodium (DSS)-induced colitis. Exosomes were isolated from the supernatant of different types of macrophages and identified via transmission electron microscopy, western blotting, and NanoSight. The results showed that M2b macrophage exosomes significantly attenuated the severity of DSS-induced colitis in mice. The number of regulatory T (Treg) cells in the spleens of mice with colitis and levels of IL-4 were both increased following treatment with M2b macrophage exosomes. In addition, key cytokines associated with colitis (IL-1β, IL-6, and IL-17A) were significantly suppressed, following treatment with M2b macrophage exosomes. The M2b macrophage exosomes exerted protective effects on DSS-induced colitis, mediated mainly by the CC chemokine 1 (CCL1)/CCR8 axis. These findings provide a novel approach for the treatment of IBD.